2001
DOI: 10.1139/o00-088
|View full text |Cite
|
Sign up to set email alerts
|

Human retinal pigment epithelium secretes a phospholipase A2 and contains two novel intracellular phospholipases A2

Abstract: The sensitivity of different phospholipase A2 (PLA2)-active fractions eluted from cation-exchange chromatography to para-bromophenacylbromide (pBPB), Ca2+-EGTA, DTT, heat, and H2SO4 indicates that human cultured retinal pigment epithelial (hRPE) cells probably contain two different intracellular PLA2 enzymes. Control experiments using "back-and-forth" thin-layer chromatography confirmed that, in our assay conditions, the generation of free fatty acids originated solely from PLA2 activity. Together with immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…There is only a little knowledge about PLA 2 expression in other parts of the eye, in addition to the retina (Castagnet and Giusto, 1993; Van Themsche et al, 2001; Kolko et al, 2007). cPLA has been identified in the human cornea (Landreville et al, 2004), while, in the conjunctiva, cPLA 2 is mainly localized in the surface of the epithelium, probably participating in the protection against risks caused by mechanical wear and tear stress (Helin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is only a little knowledge about PLA 2 expression in other parts of the eye, in addition to the retina (Castagnet and Giusto, 1993; Van Themsche et al, 2001; Kolko et al, 2007). cPLA has been identified in the human cornea (Landreville et al, 2004), while, in the conjunctiva, cPLA 2 is mainly localized in the surface of the epithelium, probably participating in the protection against risks caused by mechanical wear and tear stress (Helin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…sPLA 2 activity has been described for the retina (Castagnet and Giusto, 1993;Hanasaki and Arita, 1999), and there seems to be enhanced sPLA 2 activity in retinal ischemia and light damage (Jung and Reme, 1994;Rego et al, 1996). Furthermore, different PLA 2 s are present in the retinal pigment epithelium (Jacob et al, 1997;Van Themsche et al, 2001). To date, no PLA 2 -specific receptors have been cloned or characterized in the retina.…”
mentioning
confidence: 99%
“…PLA 2 activity has been shown to be present in the RPE (Van Themsche et al. 2001) and our previous study revealed immunohistochemical expression of rGIB in rat RPE (Kolko et al.…”
Section: Discussionmentioning
confidence: 94%
“…PLA 2 have only been investigated in the human cornea and no knowledge of PLA 2 expression in other parts of the human eye exists. However, indirect evidence points to PLA 2 activity in the outer layers of the retina (Castagnet & Giusto 1993; Van Themsche et al. 2001).…”
Section: Introductionmentioning
confidence: 99%